The Effect of the Circuit Training Model on the Endurance of Futsal Extracurricular Students - Hanafi Prasetyo; Muhammad Saleh; Wening Nugrahaeni (Journal Of Sport Education (JOPE), 2025)
This experimental study, employing a One-Group Pretest-Posttest design, evaluated the effect of circuit training on improving VO2Max capacity in 19 students participating in the futsal extracurricular program at MTs Ma’arif Assobariyyah in Sukabumi, as a solution to the athletes’ low endurance during matches. Aerobic capacity was measured before and after the intervention using the Bleep Test, with data analyzed via the Shapiro–Wilk normality test and the non-parametric Wilcoxon Signed-Rank test. The results showed a significant increase in the students’ average VO2Max values, rising from 32.92 at the pretest to 43.18 at the posttest. This significance was reinforced by the results of the Wilcoxon test, which yielded an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), thereby rejecting the null hypothesis. Thus, circuit training has been empirically proven to be effective in improving the physical fitness and aerobic endurance of futsal students. To optimize these outcomes, the study recommends full support for extracurricular activities through the provision of adequate training facilities, infrastructure improvements, and the development of a more structured training schedule. Additionally, this research is expected to serve as a theoretical reference for future researchers to conduct similar studies with a broader and more representative population.